Media Screen time, Physical Activity and Nutritional Indicators as Risk Factors for Childhood and Adolescent Overweight and Obesity in Aguas Zarcas, Costa Rica. (UNED Research Journal, 2014)
Childhood obesity is an increasingly serious issue worldwide. There is substantial research that explores health problems, psychosocial issues and rising medical costs related to obesity, however, limited research has discovered the etiology and specific risk factors associated with the epidemic. This study sought to understand the prevalence and related risk factors of obesity in rural Aguas Zarcas, Costa Rica in Spring 2011. The sample included 1 025 school-aged children ages four to 18. Each child participating in the study completed a survey that addressed hypothesized risk factors (i.e. media screen time and physical activity). I also measured each subject’s height, weight, and abdominal circumference to determine whether significant relationships existed between the proposed risk factors and the overall rate of obesity among school children. Results showed a positive relationship between screen time (time spent in front of a television, computer, or video game) and BMI/abdominal circumference and a negative relationship between physical activity and BMI/abdominal circumference. Time spent watching television on the weekend was positively correlated to BMI (p < 0,001) and physical activity throughout the week and weekend was negatively correlated with both BMI and abdominal circumference (p < 0,0001). Most children involved in the study fell within healthy height and weight classifications, while 12% were considered obese according to the Center for Disease Control’s BMI standards. Obesity rates were especially high among males and females ages ten through 12. This research serves as a foundation for further exploration of obesity risk factors and prevalence, and can be used to inform policy and programming to prevent the impending rise of childhood obesity in Costa Rica.
Keywords: obesity; risk factors; physical activity; media screen time; children; adolescents.